Impacts of Educational Factors on Entrepreneurship Intention of University Students - Thuy, Nguyen Thu (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
Drawing on the theory of planned behavior in entrepreneurship, the research proposes a model linking educational determinants, perceived entrepreneurial behavior control and entrepreneurial intentions. The model is tested with a sample of 163 students at National Economics University. The result shows that university education factors including “entrepreneurship inspiration”, “work integrated learning” and “extra curricular activities” have impact to “students’ entrepreneurial behavior control” and then “entrepreneurial behavior control” as a platform through which the educational factors have impact to “overall entrepreneurial intention”. The findings provide support to the Ajzen’s theory of planned behaviour and have wider implications for the practice of teaching in higher educational institutions. Keywords Education, entrepreneurship, university students, teaching methods, entrepreneurial intention References Becchard Béchard, J. P., and Grégoire, D., “Entrepreneurship Education Research Revisited: The Case of Higher Education”, Academy of Management Learning & Education, 4 (2005) 1, 22-38. [2] Nguyen Thu Thuy and Nguyen Ngoc Huyen, “Determinants of university students’ entrepreuourship”, Journal of Economics and Development, 7/2014. [3] Fiet, J.O., “The theoretical side of teaching entrepreneurship”, Journal of Business Venturing, 16 (2000) 1, 1-24. [4] Wu, S., Wu, L., “The impact of higher education on entrepreneurial intention of university students in China”, Journal of Small Business and Enterprise Development, 15 (2008), 752- 774. [5] Liñán, F., Chen, Y.W., “Development and Cross-Cultural Application of a Specific Instrument to Measure Entrepreneurial intentions”, Entrepreneurship Theory and Practice, 33 (2009) 3, 593-617. [6] Krueger, N.F., Reilly, M.D., Carsrud, A.L., “Competing models of entrepreneurial intentions”, Journal of Business Venturing 15 (2000) 5/6, 411-432. [7] Ajzen, I., “The theory of planned behavior”, Organizational Behavior and Human Decision Processes 50 (1991) 2, 179211. [8] Verzat, C., and Bachelet, R., “Developing and Entrepreneurial Spirit among engineering college students: What are the educational factors?”, Entrepreneurship Education, Fayolle, A., and Klandt, H., Elgar, E., (eds) chapter 11, 2006. [9] Souitaris, V., Zerbinati, S. & Al-Laham, A., “Do entrepreneurship programmes raise entrepreneurial intention of science and engineering students? The effect of learning, inspiration and resources”, Journal of Business Venturing, 22 (2007) 4, 566-591. [10] Balan, P., Metcalfe, M., “Identifying teaching methods that engage entrepreneurship students”, Education & Training, 54 (2012) 5, 368-384. [11] Vesa P. T., “Learning entrepreneurship in higher education”, Education and Training, 52 (2010) 1, 48-61. [12] El-Khasawneh, B., “Entrepreneurship Promotion at Educational Institutions: A Model Suitable for Emerging Economies”, WSEAS transactions on business and economics, 5 (2008) 2, 27-35. [13]Lüthje, C., and Franke, N., “Entrepreneurial Intentions of Business Students: A Benchmarking Study”, International Journal of Innovation and Technology Management, 1 (2004) 3, 269-288. [14] Florin, J., Karri, R., and Rossiter, N., “Fostering entrepreneurial drive in business education: An attitudinal approach”, Journal of Management Education, 31 (2007) 1, pp. 17-42. [15] Peterman, N.E. & Kennedy, J., “Enterprise Education: Influencing Students’ Perceptions of Entrepreneurship”, Entrepreneurship Theory and Practice, 28 (2003) 9 2, 129-144.